2002
DOI: 10.1152/ajpendo.00032.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of human liver, kidney, and skeletal muscle in postprandial glucose homeostasis

Abstract: . Role of human liver, kidney, and skeletal muscle in postprandial glucose homeostasis. Am J Physiol Endocrinol Metab 282: E419-E427, 2002; 10.1152/ ajpendo.00032.2001.-Recent studies indicate a role for the kidney in postabsorptive glucose homeostasis. The present studies were undertaken to evaluate the role of the kidney in postprandial glucose homeostasis and to compare its contribution to that of liver and skeletal muscle. Accordingly, we used the double isotope technique along with forearm and renal bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
163
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(178 citation statements)
references
References 55 publications
4
163
0
9
Order By: Relevance
“…The kidneys mainly play an important role in maintaining body fluid and water homeostasis, as well as glucose production. [50][51][52][53] Obesity may potentiate the development and progression of secondary focal segmental glomerulosclerosis. 54,55 Recently, circadian-clock genes were shown to act on E-box elements present in the promoter region of the NHE3 and to play a direct role in regulating NHE3 gene expression in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The kidneys mainly play an important role in maintaining body fluid and water homeostasis, as well as glucose production. [50][51][52][53] Obesity may potentiate the development and progression of secondary focal segmental glomerulosclerosis. 54,55 Recently, circadian-clock genes were shown to act on E-box elements present in the promoter region of the NHE3 and to play a direct role in regulating NHE3 gene expression in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…After meal ingestion, endogenous glucose production decreases, and the ingested carbohydrate load is taken up by various tissues, mainly the liver and muscles (42,66). The role of the kidney in postprandial glucose metabolism has recently been investigated (67). Seemingly, renal glucose release paradoxically increases postprandially and it accounts for Ͼ50% of the endogenous glucose release for several hours.…”
Section: Renal Glucose Metabolism In the Postprandialmentioning
confidence: 99%
“…The mechanism responsible for this increase in renal glucose release remains to be determined, but it could involve postprandial increases in sympathetic nervous system activity (68) and increases in the availability of gluconeogenic precursors (e.g., lactate and amino acids). Renal glucose uptake apparently does not play a major role in postprandial glucose uptake, because it accounted for Ͻ10% of the disposition of the ingested glucose load (67).…”
Section: Renal Glucose Metabolism In the Postprandialmentioning
confidence: 99%
“…All those 25 donors had evidence of different types and stages of diabetic retinopathy. The male percentage of them was 56.3%, the mean interval between kidney donation, and development of high albuminuria, very high albuminuria, and/or decreased creatinine clearance was 10.1 ± 4.6 years (range, 4-21 y) and the mean interval between the development of DM and high albuminuria, very high albuminuria, and or decreased eGFR below 70 mL/min was 6 ± 3.9 y (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The percentage of high albuminuria, very high albuminuria, and/or decreased creatinine clearance below 70 mL/min is significantly higher in our study than a UKPDS64 study, which showed 30.8% in a study of 5100 T2DM patients with 2 kidneys enrolled in it.…”
Section: Discussionmentioning
confidence: 99%
“…Yet traditionally, the kidneys have not been considered an important source of glucose (except during acidosis or after prolonged fasting), with most clinical discussions on glucose dysregulation centering on the intestine, pancreas, liver, adipose tissue, and muscle. 2 However, the significance of the kidneys' contribution to glucose homeostasis, under both physiologic and pathologic conditions, has become well-recognized, and is thought to involve functions beyond glucose uptake and release. Besides the liver, the kidney is the only organ capable of generating sufficient glucose (gluconeogenesis) to release into the circulation, and it is also responsible for filtration and subsequent reabsorption or excretion of glucose.…”
Section: Introductionmentioning
confidence: 99%